The Little Book of Chess Tips - French, Peter (England Absolute Press, 2007)
Suitable for Chess fanatics, this book includes tactical and strategic tips and useful game principles and memory aids. It helps you learn how to study your opponent's game plan, how to develop your own and how to remain alert throughout. It shows you how best to control the centre and dictate play and the effective way of keeping your King safe.
Keywords: Chess